Zikri Online Gadget / Muhammad Zikri Hakim Zakaria - Zakaria, Muhammad Zikri Hakim (2021)
Various types of devices are available in Zikri online gadgets to meet the daily needs of users. Zikri online gadgets also cater to the busy public and students, as we provide product delivery services to universities and residences, using the concept of cash payment and online banking. Our products are accessible at online platform and our residence located in Hutan Melintang.Perak. It is more convenient to handle our goods when our target consumers are close to make cash on delivery services and more reliable when customer ordered in online platform that make more easier to customer waiting the parcel arrive front of their house. I also established Facebook to grow my company via social media and learnt how to publish Facebook for business goods such teaser advertisements, soft sales, etc.